The Romanian generation y: Preparing today’s students for tomorrow’s job market - VASILESCU, Ruxandra (Annals of Spiru Haret University. Economic Series, 2016)
Who are they, what do they want, but most of all, where are they? Teaching for the generation Y is a total challenge for today’s teachers. But become acquainted with the habits and expectations of the Generation Next might help us to bring them back into the classroom and train them properly for the job market. It is imperative to understand the new directions set by Generation Y itself, on their terms, to develop a methodology that might ensure their future success. This paper is a comparison of the members of the so-called Generation Y in the USA, Europe and Romania, their different environment and expectations, with a particular focus on the Romanian GenY and the students of Spiru Haret University.